Investigation of bacterial cellulose-based hybrid aerogels as consequence of drying techniques and functionalization - Marchiori, Leonardo. [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Aerogel’s microstructure, kept intact by supercritical drying, affects its properties beyond its chemical composition. Nowadays, aerogels are essential in different industries, like thermal insulation, high-efficiency batteries, and aerospace applications. Nevertheless, aerogels rapidly reach mass production, while their fundamental studies and particularities were partially left behind. On the other hand, cellulose is a natural polymer that has been studied for decades, composed of glucose units, and can be obtained by different approaches, but via bacterial production yields a higher purity and crystallinity biopolymer. Structured by intertwined fibers, which possess nanometric diameters and micrometric length, materials based on bacterial cellulose have mechanical strength, flexibility, interconnected pore structure, and relatively high surface area. Due to its properties, transforming bacterial cellulose gel to aerogel, preserving its morphological features, is of great interest to a vast range of applications, adsorption and catalysis are examples. Cellulose itself does not show great adsorption capability for different molecules, nor for catalysis, but it can be associated with nanomaterials as a support, enhancing nanomaterial applications. Taking advantage of cellulose properties, they can be employed as membranes or sphere-like particles, allowing in-flow applications and suspended particles, achieving feasible recovery, contrasting nanomaterials' common drawback, aside from the nanoscale-related toxicity. Arising from synergism between cellulose, aerogels, and nanomaterials studies, the thesis starts with a focus on the different properties obtained when obtained the biopolymer is dried under different drying techniques, and evaluating their surface properties as well as their adsorption and photocatalytic applications. Analyzing literature gaps on aerogels, both on definition and fundamental studies, it was proposed an updated aerogel’s definition, as well as its interpretation. After exploring the influence of drying technique on gels’ preparation, the next chapter aimed to explore how a silica-based gel grows onto bacterial cellulose, a gel formed by two different alkoxy-silane precursors, impact aerogel’s REE sorption and selectivity. One precursor had four hydrolysable groups, and the other had an organic chain substitution, guarantying ethylenediamine functionalization. While the first precursor could only result in silica oxide structure, presenting surface metalol groups, the other precursor had metal-coordinating and adsorbing groups, guiding their application. Lastly, after studying means of materials preparation with drying technique and functionalization, bacterial cellulose aerogels were coated with titania and were applied to investigate the chemical stability of bacterial cellulose. Titania, a known oxidizing material upon ultraviolet light irradiation, once coating cellulose fibers, is capable not only of oxidizing organic molecules, but also of oxidizing cellulose itself, the inner material used as support. Result never seen in literature. Finally, the results obtained on this thesis abord bacterial cellulose aerogels in different aspects, from its biosynthesis, to preparation of the dried gels. Given highlights to the functionalization with silica-based gel, for distinct applications, and lastly shown the first study of bacterial cellulose oxidation under a photocatalytic process. Contributing not only with cellulose studies, but to material science as a broader area.
Investigação de aerogéis híbridos em celulose bacteriana decorrente de técnicas de secagens e funcionalização
Keywords: Sol-gel properties; Polymeric networks; Semiconductors; Photocatalysis; Silica gel; Processo sol-gel; Redes de polímeros; Semicondutores; Colóides; Fotocatalise